PHARMACEUTICO THERAPEUTICS OF SHADBINDU THAILA - A CASE STUDY ON EFFICACY IN TIMIRA W.S.R. TO MYOPIA (International Journal of Ayurveda and Pharma Research, 2020)
Nasyakarma is one among the Panchakarma procedures in which, the medicated drugs are administered through the nasal route and is indicated specially for the treatment of Urdhwajathrugatharogas i.e., the disorders of head and neck. Prathimarsha nasya is a type of Nasya wherein the medicament is administered in smaller dosage and advisable in all age groups and conditions. Material and methods: Shadbindhu taila containing different Vatahara and Kaphahara drugs processed along with Ajakshira was prepared in the laboratory of Rasashatra and Bhaishajyakalpana of SDM college of Ayurveda, Udupi, as per the classical reference and with all precautions. Single case study was taken up in a patient diagnosed of Timira viz myopia. Results and discussion: Shadbindhu taila is Tikta – katu rasa, Madhuravipaka, having Ushnathikshnaguna. It helps in decreasing the excessive secretions from the mucus membrane of nose, dryness as well as the inflammation of the nose. It is useful in strengthening the functions of eyes, growth of hair, maintaining the integrity of the teeth. A single case study was taken up to access its efficacy in Timira w.s.r. myopia and it is found to have promising results. Conclusion: Shadbindhu taila has shown improvement in the patient when used in the form of Prathimarsha nasya. Further study with larger sample size has to be done and with different stages of myopia can be done for further evaluation.